The mediating role of physical activity and health status between a health-supportive environment and well-being: a cross-sectional study - Liao, Yi; Cheng, Xiaoyu; Li, Zhuangzhuang; Li, Yanyan (Frontiers in Public Health, 2023)
Objective: Based on the social-ecological systems theory and social support theory, this study aims to explore the relationship between a health-supportive environment and well-being among residents.It further examined the mediating role of physical activity and health status in the pathway between a health-supportive environment and well-being.The study utilized data from 2,717 samples of the China General Social Survey (2021) and conducted multiple regression analysis and mediation analysis using statistical software Stata 16.0 and SPSS PROCESS 3.3.(1) A health-supportive environment had a significant impact on residents' well-being (t=8.476, p<0.001). (2) Among the three dimensions of natural environment, built environment, and neighborhood social environment, the influence of neighborhood social relationship environment had the strongest influence on residents' well-being (t=8.443, p<0.001). (3) Physical activity and health status played a mediating role in the relationship between a health-supportive environment and residents' well-being. The mediating effect was as follows: health-supportive environment → physical activity → well-being with a mediation effect of 0.020; health-supportive environment → health status → well-being with a mediation effect of 0.029; health-supportive environment → physical activity → health status → well-being with a mediation effect of 0.008.A health-supportive environment not only directly influences residents' well-being but also indirectly affects it through physical activity and health status. It is essential to focus on improving both the natural and built environment as well as the neighborhood social relationship environment in enhancing residents' well-being. Physical activity serves as an important means to improve residents' health level and promote their well-being.